Os espelhos das exclusões radicais : o mundo prisional feminino brasileiro visto do outro lado da linha abissal - Carvalho, Claudia Cristina Ferreira (2017)
This investigation, a critique of postcolonial feminist theories, starts from the perspective that the fabrication of the feminine Other as the other masculine, feeds from an abyssal thought, which either obliterated or obliterates, or systematically produced absences, introduced a subaltern violence of a masculine gender towards the feminine gender, constructing radical lines of social exclusion. This system of oppression, which is denominated hetero-patriarchal, was not born within western modernity, but it was undoubtedly formes by two other logics of oppression, that are colonialism and capitalism, to reify on the one hand, men as the center and measure of all things; On the other, women as the periphery of those who imagine themselves as the center (men). Accordingly to this logic, women have their voices muted, their ontology and epistemology wasted and invisible. Thus, this research analyzed the comprehensive interpretative dimensions of intersubjective interactions constructed by subalternized women inside a Brazilian female penitentiary, both those in condition of confinement and the workers of that prison system. The Southern Epistemologies, proposed by Boaventura de Sousa Santos, were used to explore the ruins of what has been produced as a sociology of absences and emergencies. On the one hand, the objective was to problematize the formulations of institutional knowledge-power in the ordinary processes sculpted out of the interactions between working women and women in confinement. On the other hand, it was analyzed in that prison space-time, converted into the dehumanization of the Other, as women in condition os confinement create knowledges of resistances-resilences explicits or not, born from the struggle and suffering. Central hypothesis, the prison fulfills a socio-political role of continuity and reiteration of the radical exclusions generated by the capitalist, colonial and patriarchal systems of oppression. Systems that generate and manage abyssal lines, which by division, obliterate the sociabilities they generate. The empirical investigation‟s essence was the qualitative research of ethnographic approach, and in its core, joined a triangular procedure of observation, interviews and iconographies (images) produced based on the proposed and accepted strategy of a photography course given to women who wished to participate. The immersion in the field of the research lasted for eleven months. The interpretative understanding of the scale of the phenomenon under study was delimited under an ecology of knowledge, translated into five nuclear central epistemic, political and ontological that was problematized: the ways in which formal and non-formal cartography sculpted the prison space-time; How the processes of imprisonment in the prison institution reflected the mirrors of radical exclusions characterized by the dichotomy between formal equality and real inequality; Institutional knowledge was discussed as an ordinary process of appropriation and violence; From the personal experiences of women in imprisonment, approaches such as gender violence reverberate in female incarceration processes; The forms of resistance and resiliency and the knowledge built by the subalternized women of the penitentiary out of struggle and suffering became visible. The epistemic, ontological and political contribution of the thesis is to perceive the social and cognitive injustices to which the subalternized women of the Southglobal are exposed, while contributing to the debate of postcolonial feminisms, mobilizing new questions for old socio-political problems and culture.